2003
DOI: 10.1071/ea02229
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic resistance in sheep nematodes in Australia: the need for new approaches

Abstract: Sheep worm infections increasingly threaten the profitability of the Australian sheep industry as the prevalence and severity of anthelmintic resistance continues to rise. Field experiments have demonstrated that the use of drenches that are of reduced efficacy due to resistance can reduce wool production by 10% and significantly reduce sheep sale value. The major factor in benzimidazole (BZ) and levamisole (LV) resistance, and in part macrocyclic lactone (ML) resistance in Haemonchus contortus, is considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(119 citation statements)
references
References 42 publications
3
114
0
2
Order By: Relevance
“…The trend continued with the introduction of a new generation of drugs in the same class as well as other classes like imidathiazole and macrocyclic lactones. This has led to the development of multiple drug resistant (MDR) strains of H. contortus in many parts of the world viz., South America (Nari et al 1996), South Africa (van Wyk et al 1999, Malaysia (Chandrawathani et al 2003), Southeast USA (Mortensen et al 2003), Australia (Besier and Love 2003), New Zealand (Leathwick et al 2001) and India (Gill 1996;Swarnkar et al 1999;Easwaran et al 2009). In Tiwari et al (2006) reported the prevalence rate of BZ resistance in H. contortus of Indian isolates by RFLP-PCR technique.…”
Section: Discussionmentioning
confidence: 99%
“…The trend continued with the introduction of a new generation of drugs in the same class as well as other classes like imidathiazole and macrocyclic lactones. This has led to the development of multiple drug resistant (MDR) strains of H. contortus in many parts of the world viz., South America (Nari et al 1996), South Africa (van Wyk et al 1999, Malaysia (Chandrawathani et al 2003), Southeast USA (Mortensen et al 2003), Australia (Besier and Love 2003), New Zealand (Leathwick et al 2001) and India (Gill 1996;Swarnkar et al 1999;Easwaran et al 2009). In Tiwari et al (2006) reported the prevalence rate of BZ resistance in H. contortus of Indian isolates by RFLP-PCR technique.…”
Section: Discussionmentioning
confidence: 99%
“…Effective targeting should also lead to an increased interval between treatments, allowing susceptible genotypes a better opportunity to establish on pasture and so reduce the risk of heterozygotes mating and producing homozygous resistant offspring. Recent examples of the use of targeted treatments include studies conducted in Western Australia (Besier and Love, 2003) and Italy (Cringoli et al, 2008) where treatments were stopped during summer months when few parasites were present on pasture and given instead at other times when more parasites were present in refugia.…”
Section: Targeted Treatmentsmentioning
confidence: 99%
“…Costs arising from these components have been quantified for the UK sheep to be approaching d100 million per year (Nieuwhof and Bishop, 2005). Control is largely based around anthelmintic usage; however, the development of anthelmintic resistance in nematode populations has fast become an international problem (Besier and Love, 2003;Bartley et al, 2004). This has led to the need for new control measures, such as selection for increased nematode resistance, with available field data (for example, Kemper et al, 2010), suggesting that such selection should be successful.…”
Section: Introductionmentioning
confidence: 99%